An overview of the diversity of Asian Elephants in Indonesia in Terms of Their Genetics - Ilyas, Syafruddin (International Journal of Ecophysiology, 2022)
There are two species diversity of Asian elephants in Indonesia, namely: Sumatran elephant (Elephas maximus sumatranus) and Borneo elephant (Elephas maximus borneensis). This literature study aims to identify and analyze the diversity of Asian elephants in Indonesia, namely: Sumatran elephants (Elephas maximus sumatranus) and Borneo elephants (Elephas maximus borneensis) as seen from their genetics (Microsatellites). This elephant is listed in the red list book of the International Union for Conservation of Nature (IUCN) from precarious to critically endangered. Meanwhile, the Borneo Elephant (Elephas maximus borneensis) is included in the IUCN red list with the endangered category. The Amely gene of the Sumatran elephant’s Y chromosome is used to trace offspring paternally. Meanwhile, Borneo elephants have low genetic diversity due to the low average number of alleles and heterezygotes and genetic research on Borneo elephants is also still small. For this reason, it is necessary to make further conservation efforts to maintain the Borneo elephant species that have unique characteristics. This Borneo elephant is a unique species, because it is smaller or dwarf in size than other elephants, with straight tusks and has a long tail